Analisis SWOT dalam Pengembangan Strategi Pemasaran Pada Usaha Outdoor Tools Store (OTS) di Watampone - Arisman Jaya; Irmayani; Anis; Otong Karyono (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
The recent increase in tourism trends has become an opportunity for business people to take advantage of this. This is marked by the emergence of various shops selling and renting outdoor equipment and equipment and among the many outdoor equipment shops that are growing and developing is the Outdoor Tools Store in Watampone. Therefore, the aim of this research is to carry out a SWOT analysis in developing marketing strategies for this business. This research is a type of qualitative research. So the research data in the research is qualitative data. Data collection was carried out using interviews, documentation and observation. The research results show that in developing a marketing strategy for the Outdoor Tools Store (OTS), it is necessary to offer equipment at affordable prices amidst market competition, provide optimal service for all customer needs, provide a comfortable shopping and rental experience to customers, and utilize stock monitoring technology to respond rapid changes in demand in the market.